[tex]\underbrace{(12x^5y+12x^6y-3y^5-18xy^5)}_M\,\mathrm dx+\underbrace{(2x^6-15xy^4)}_N\,\mathrm dy=0[/tex]
[tex]M_y=12x^5+12x^6-15y^4-90xy^4[/tex]
[tex]N_x=12x^5-15y^4[/tex]
[tex]-\dfrac{N_x-M_y}N=6\implies\mu(x)=\exp\left(\displaystyle\int6\,\mathrm dx\right)=e^{6x}[/tex]
[tex]\underbrace{(12x^5y+12x^6y-3y^5-18xy^5)e^{6x}}_{\mu M}\,\mathrm dx+\underbrace{(2x^6-15xy^4)e^{6x}}_{\mu N}\,\mathrm dy=0[/tex]
You can verify that the partial derivatives are equal.
[tex]F_x=\mu M[/tex]
[tex]F=(2x^6y-3xy^5)e^{6x}+f(y)[/tex]
[tex]F_y=\mu N[/tex]
[tex](2x^6-15xy^4)e^{6x}+f'(y)=(2x^6-15xy^4)e^{6x}[/tex]
[tex]f'(y)=0[/tex]
[tex]\implies f(y)=C[/tex]
[tex]\implies F(x,y)=(2x^6y-3xy^5)e^{6x}=C[/tex]